Innovative Approach to Graphene Film Synthesis: Factorial Design in PECVD Experiments - Pitjamit, Siwasit; Vichiansan, Norrapon; Leksakul, Komgrit (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Graphene, a two-dimensional carbon allotrope, has garnered significant interest due to its exceptional properties and diverse applications. This study investigates the optimization of graphene synthesis parameters using plasma-enhanced chemical vapor deposition (PECVD) to enhance film properties and broaden their application potentials. Using a comprehensive factorial design approach, factors including electric power (ranging from 60 to 100 W), the acetylene-to-hydrogen ratio (ranging from 30:70 to 50:50), and discharge time (ranging from 10 to 30 minutes) were systematically varied, and film thickness and the D/G ratio served as response variables. The experimental results revealed the significant effects of these parameters on film thickness, with optimal conditions identified as an electric power of 100 W, an acetylene-to-hydrogen ratio of 50:50, and a discharge time of 10 min. The average film thickness ranged from 41.51 to 253.80 nm. Morphological and structural analyses using atomic force microscopy and Raman spectroscopy elucidated the impact of synthesis parameters on film characteristics, with the D/G ratio varying from 0.75 to 1.8, indicating the degree of graphitization and defect density. Furthermore, surface properties and wettability were assessed using contact angle measurements, providing insights into surface interactions crucial for various applications. This study culminates in discussions on the implications for graphene synthesis optimization and its potential applications across diverse fields. Overall, this research contributes to advancing the understanding of graphene synthesis methodologies and underscores its significance in driving technological innovations.